Management of Mobile Training Unit in Youth Empowerment in Mushroom Cultivation Training at Upt Jember Regency Job Training Center - Rakadewa, Elang; Hendrawijaya, A.T; Indrianti, Deditiani Tri (Universitas Pendidikan Indonesia (UPI), 2023)
In modern times today there are many problems that arise in society, one of which is the difficulty in finding a job due to lack of provisions or experience. Training is very important for our lives. Nowadays there are very many training institutions that have begun to emerge in big cities, therefore a new innovation has emerged, namely the Mobile Training Unit (MTU) for those who are difficult to reach the training location. This study used a qualitative research approach. UPT Jember Regency Job Training Center as a research site using purposive area, observation, interviews, and documentation. As for the technique of determining research informants using snowball sampling, the key informants of this research are MTU program managers, and supporting informants are MTU participants. Data analysis was carried out using the Miles and Huberman model, namely data collection, data reduction, data presentation, and conclusion. The conclusion of this study is that the management carried out by instructors from UPT Job Training Center has been effective and efficient in empowering trainees.